2021
DOI: 10.3389/fpsyt.2021.802581
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of the Serotonin System in Major Depression

Abstract: Serotonin is a key neurotransmitter that is implicated in a wide variety of behavioral and cognitive phenotypes. Originating in the raphe nuclei, 5-HT neurons project widely to innervate many brain regions implicated in the functions. During the development of the brain, as serotonin axons project and innervate brain regions, there is evidence that 5-HT plays key roles in wiring the developing brain, both by modulating 5-HT innervation and by influencing synaptic organization within corticolimbic structures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 264 publications
(263 reference statements)
0
29
0
1
Order By: Relevance
“…Indeed, deficits in serotonergic transmission, including reductions in 5-HT neurons and their projections, are associated with this disease and failure of antidepressant responses. Additionally, the most commonly prescribed antidepressants are based on the blockade of 5-HT transporter (5-HTT or SERT), increasing the levels of 5-HT on the synaptic cleft, promoting antidepressant responses [ 6 , 24 ]. MAO enzyme imbalances are also associated with the pathology of depression.…”
Section: Trp Metabolism In Depression—an Overlookmentioning
confidence: 99%
“…Indeed, deficits in serotonergic transmission, including reductions in 5-HT neurons and their projections, are associated with this disease and failure of antidepressant responses. Additionally, the most commonly prescribed antidepressants are based on the blockade of 5-HT transporter (5-HTT or SERT), increasing the levels of 5-HT on the synaptic cleft, promoting antidepressant responses [ 6 , 24 ]. MAO enzyme imbalances are also associated with the pathology of depression.…”
Section: Trp Metabolism In Depression—an Overlookmentioning
confidence: 99%
“…Serotonin (5-HT) is one of the most influential neuromodulators regulating PFC activity state and synaptic plasticity throughout the entire lifespan, including in the early life ages 17 , 18 . In the mammalian brain, serotonergic neurons are among the first cells to differentiate during postnatal development 19 .…”
Section: Introductionmentioning
confidence: 99%
“…This property could play a key role in shaping primordial circuits that define cortical functions 6,[13][14][15] . In this respect, it has recently been reported that impairment of excitatory activity during early life leads to reduced dendritic arborization, decreased dendritic spine density, and alterations in circuit formation, which are accompanied by cognitive deficits and maladaptive behaviors 11,16 .Serotonin (5-HT) is one of the most influential neuromodulators regulating PFC activity state and synaptic plasticity throughout the entire lifespan, including in the early life ages 17,18 . In the mammalian brain, serotonergic neurons are among the first cells to differentiate during postnatal development 19 .…”
mentioning
confidence: 99%
“…However, whether binge alcohol consumption dysregulates social recognition and arousal behavior in adult rodents has not been explored. The brain's serotonin (5-hydroxytryptamine, 5-HT) system is a critical modulator of affect, motivation, social behavior, arousal, and metabolism (da Cunha-Bang and Knudsen, 2021;Georgescu et al, 2021;Hayes and Greenshaw, 2011;Vahid-Ansari and Albert, 2021). Dysregulation of 5-HT signaling has been implicated in the pathophysiology of numerous psychiatric disorders, including major depression, anxiety disorders, substance use disorders, obsessive-compulsive disorder, and schizophrenia (Nordquist and Oreland, 2010).…”
Section: Introductionmentioning
confidence: 99%